Eï¬€ect of Zinc(II)-2,4,5-triphenyl-1H-imidazole Complex Against Replication DENV-2 in Vero Cell - Sucipto, Teguh Hari; Wibrianto, Aswandi; Martak, Fahimah; Churrotin, Siti; Amarullah, Ilham Harlan; Setyawati, Harsasi; Wardhani, Puspa; Aryati, Aryati; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2020)
Dengue virus (DENV) is a significant pathogen emerging worldwide as a cause of infectious disease. DENVs are transmitted to humans through female mosquitoes from Aedes aegypti and Aedes albopictus species. Indonesia is one of the largest countries in the world in dengue endemic regions worldwide. Dengue fever was occurred for the first time as an outbreak in Surabaya and Jakarta in 1968. Many eï¬€orts have been made to prevent and treat DENV infections, and clinical trials of a number of vaccines are currently underway. Antiviral testing of DENV is an important alternative for drug characterization and development. Complex compounds are formed as a result of metal and organic complex reactions. Complex compounds can be used as an anti-inflammatory, antimicrobial antifungal, antibacterial, antivirus. The Zn2+ ion can be used as an antiviral candidate. The purpose of this project was investigated Zinc(II)-2,4,5-triphenyl-1H-imidazole antiviral compound to be further tested for inhibitory eï¬€ect on the replication of DENV-2 in cell culture. DENV replication was measured by antiviral activity assay and cytotoxicity assay. The inhibitory activity of Zinc(II)-2,4,5-triphenyl-1H-imidazole complex compound was determined by Viral ToxGloTM Assay. The cytotoxicity of Zinc(II)-2,4,5-triphenyl-1H-imidazole complex compound was determined by CellTiter96® AQuoeus assay. The inhibitory concentration (IC50) of Zinc(II)-2,4,5-triphenyl- 1H-imidazole against dengue virus type-2 was 34.42 Î¼g/ml. The cytotoxic concentration (CC50) of compound against Vero cell was <100 Î¼g/ml. The results of this study demonstrate the antidengue serotype 2 inhibitory activity of investigated Zinc(II)-2,4,5-triphenyl-1H-imidazole complex and its high toxicity in Vero cells. Further studies are not required before investigated Zinc(II)-2,4,5-triphenylimidazole can be applied in the treatment of DENV-2 infections